Studi Recovery Tembaga pada Proses Froth Flotation dari Bijih Tembaga Papua, Indonesia dengan Variasi pH dan Konsentrasi Kolektor - Heimbach, Ivano; Petrus, Himawan Tri Bayu Murti; Prasetya, Agus; Idrus, Arifudin; Timotius, Daniel; Kusumastuti, Yuni; Sutijan, Sutijan (Prosiding Seminar Nasional Teknik Kimia "Kejuangan", 2023)
In the process of flotation of copper-bearing ore, several factors such as the concentration of the collector used and the pH of the fluid used can have an impact. In this study, observations were made on the influence of collector concentration and pH on the recovery of copper ores from Papua, Indonesia. The ore samples were obtained from three different site. Preparation of samples were conducted by crushing and sieving to obtain solid particles with a size of +200 mesh. The fine particles then fed into froth flotation device. Froth flotation operations were carried out at different operating condition namely pH (pH 3, pH 6, and pH 9), xanthate concentration (1300, 2000, and 2600 ppm), and time (3, 5, 7, and 14 minutes). The froth and tailings were collected separately and dried in an oven at 60oC. The feed, froth, and tailings were then subjected to EDX analysis to determine their compositions. The results of the experiment showed that higher collector concentrations did not necessarily lead to increased copper recovery. The appropriate pH conditions, however, could optimize copper recovery. The optimum conditions obtained from this experiment were xanthate concentration of 2000 ppm, pH of 3, and the ore sample 2